The effect of red guava juice provision on hemoglobin levels in anemic pregnant women - Kusuma Wardani, Fina; Harahap, Hasanah Pratiwi; Nasution, Yulida Effendi (Journal of Midwifery and Nursing, 2024)
During pregnancy, women must maintain nutritional intake to avoid anemia. Anemia occurs due to lack of iron, folic acid, and vitamin B12. To increase hemoglobin levels in the body, non-pharmacological therapy can be done by consuming red guava juice. This study aimed to determine the difference in hemoglobin levels before and after giving red guava to pregnant women with anemia. This study uses a pre-experimental method with a one group pretest posttest design. The population in this study was all pregnant women in second trimester with the incidence of anemia at Dina Maternity Home Medan. The sample in this study was 10 pregnant women with mild anemia taken by purposive sampling technique. Analysis of univariate and bivariate data was done by using paired sample T-test. The results showed that the hemoglobin level before administration of red guava juice had a mean value of 10.01 g/dl, while the hemoglobin level after administration of red guava juice had a mean value of 11.68 g/dl, with a mean difference of -1.670 and p-value 0.000. The conclusion of this study showed that there was a difference in the effect of giving red guava juice on hemoglobin levels in anemic pregnant women.